Association between various cathepsins and uterine leiomyoma: A Mendelian randomization analysis - Liu, Tingxiu; Ren, Yuehan; Zhang, Junning; Yin, Hechun; Zheng, Zheng; Zhang, Mingyue; Liao, Yan; Yang, Liangliang; Liu, Chang; Liu, Xinmin; Yan, Peiyu (PLOS ONE, 2024)
Emerging evidence suggests a tentative association between cathepsins and uterine leiomyoma (UL). Previous investigations have predominantly focused on the role of cathepsins in the metastasis and colonization of gynecological malignancies. Still, observational studies may lead to confounding and biases. We employed a bidirectional Mendelian randomization (MR) analysis to elucidate the causative links between various cathepsins and UL. Instrumental variables (IVs) of cathepsins and UL within the European cohort were from extant genome-wide association study datasets. Sensitivity assessments was executed, and the heterogeneity of the findings was meticulously dissected to affirm the solidity of the outcomes. Our findings reveal the association between cathepsin B (CTSB) and an elevated risk of developing UL (all cancers excluded) [Inverse Variance Weighted (IVW) method]: OR = 1.06, 95%CI [1.02, 1.11], P = 0.008895711. Although the association does not persist after multiple testing or Steiger filtering, this finding adds to our understanding of the causal relationship between CTSB of various cathepsins and UL (all cancers excluded) and may herald new therapeutic avenues for individuals affected by this condition.